Cooperative vocabulary learning strategies among undergraduate students at higher learning institutions in Malaysia - Muhamad Syahir Saifudin
Vocabulary is vital to be mastered by second language learners of English, as it would enable them to converse in English proficiently. However, the process of learning a new language is difficult as they often lack knowledge of the correct learning strategies to master vocabulary. Many researchers indicated that the use of effective vocabulary learning strategies in learning English may assist students greatly in improving their vocabulary knowledge. Cognitive vocabulary learning strategies are commonly used by many students. However, cooperative vocabulary learning strategy is rarely used by the students although its efficiency in improving learners' vocabulary mastery in the long run is proven through many past researches. Thus, this study aims to investigate the use of cooperative vocabulary learning strategies among undergraduate students in higher learning institutions in Malaysia. This mixed method study employed both quantitative and qualitative method to collect data. The respondents comprised 75 undergraduate students who were undergoing an English course at three different universities, which are Universiti Sultan Zainal Abidin (UniSZA), Universiti Teknologi Mara Shah Alam (UiTM), and Institute of Teacher Education Campus Dato' Razali Ismail. They were recruited using purposeful sampling method. The Likert Scale survey questionnaire was used to collect the quantitative data, while interviews were conducted with the respondents to obtain qualitative responses. The Statistical Package for the Social Sciences (SPSS) version 22.0 was employed to analyse the statistical data, while the interview responses were analysed manually. Results showed that all respondents relied on certain vocabulary learning strategies in mastering vocabulary. Memory strategy, social strategy, cognitive strategy, meta-cognitive strategy and determiner strategy were found to play a very significant role in enhancing the vocabulary learning of the respondents. However, it was found that memory strategy was the most used strategy and social strategy was the least strategy used by the learners. Based on the interview responses; however, the respondents agreed that cooperative learning strategy played the most significant role in learning vocabulary. The study concludes that vocabulary learning strategies are beneficial in improving students' vocabulary efficiency for they are vital in expediting students' vocabulary learning process. Students are expected to be more active and productive during their learning process if the vocabulary learning strategies are taught explicitly in classroom. The findings of the study may contribute significantly to the body of knowledge in terms of theory, pedagogy and methodology conclusively.